Poland - (James Albert). 1907-1997. Michener, James A. (Editorial Random House, 1983)
Poland's history from the thirteenth century to modern times overshadows a 1981 dispute between Janko Buk, the leader of a group of militant farmers, and Szymon Bukowski, the communist Minister of Agriculture